2012
DOI: 10.1002/ejoc.201200928
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Chiral Multi‐Functionalized Polyheterocyclic Benzopyran Derivatives by Using an Asymmetric Organocatalytic Domino Reaction

Abstract: The asymmetric domino reaction of various α,α‐dicyano olefins to 3‐nitro‐2H‐chromenes was studied employing readily available cinchona‐derived bifunctional thioureas as organocatalysts. These new transformations were highly regio‐, chemo‐, diastereo‐, and enantioselective simultaneously giving chiral multi‐functionalized polyheterocyclic benzopyran derivatives with multi‐chiral carbon centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…1); the stereochemistry of 5 was confirmed by the crystallographic analysis. 11 This indicated that in the case of 2b spontaneous aromatization does not proceed.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1); the stereochemistry of 5 was confirmed by the crystallographic analysis. 11 This indicated that in the case of 2b spontaneous aromatization does not proceed.…”
Section: Resultsmentioning
confidence: 98%
“…10 Xie et al obtained the dibenzo [b,d]pyrans by the domino reaction starting from 2-aryl-3-nitro-2H-chromenes and ylidenemalononitriles. 10,11 This promising approach deserves further investigations in order to expand the scope of its possible applications. 12 Herein we wish to demonstrate utility of readily available 3-nitro-2-(trifluoromethyl)-2H-chromenes 1 as valuable building blocks for the construction of dibenzo [b,d]pyrans bearing a CF 3 group at the 6-position via a formal [4þ2] cycloaddition of 2-(1-phenylethylidene)malononitrile (2a) and 2-(1-phenylpropylidene)malononitrile (2b).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge this is the first example of a catalytic enantioselective access to spirocyclic cyclohexenimines, expanding the arena of pyrazolinone based spirocyclohexane derivatives, potentially useful in medicinal chemistry. [27] Mild reaction conditions, commercial availability of the organocatalyst and feasibility of scale-up process are other attractive features of the process.…”
Section: Abstract: Asymmetric Synthesis; Organocatalysis; Spirocyclicmentioning
confidence: 99%
“…1). Alkylidene malononitriles [15][16] can serve as four-carbon starting materials for the synthesis of cyclic compounds. With the ongoing interest in the construction of valuable aromatic polycyclic compounds using electron-deficient heteroaromatics, [17] we envisioned that the dibenzofuran derivatives 3 could be synthesized via a base promoted benzannulation [18] of 2-nitrobenzofurans 1 with alkylidene malononitriles 2 (Scheme 1B, eq.…”
Section: Introductionmentioning
confidence: 99%
“…[13c-d] The structure of product was further confirmed by the X-ray analysis of a single crystal of 3 ea (See Supporting Information). [23] Based on the experimental results and previous studies, [13,[15][16] the mechanism proposed for the synthesis of dibenzofuran derivatives 3 is shown in Scheme 4. The alkylidene malononitriles 2 was initially deprotonated by K 2 CO 3 to yield anion A, which reacted with 2-nitrobenzofurans 1 via vinylogous conjugate addition and cyclization cascade to produce the intermediate B.…”
Section: Introductionmentioning
confidence: 99%